1994
DOI: 10.1056/nejm199409153311104
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Hypercholesterolemic Response to a High-Cholesterol Diet in Subjects Heterozygous for the Apolipoprotein A-IV-2 Allele

Abstract: The apo A-IV-2 allele attenuates the hypercholesterolemic response to the short-term ingestion of a very-high-cholesterol diet and may partially account for the heterogeneous response to dietary cholesterol. However, cholesterol intake in this study was more than twice that of the general population; whether the apo A-IV-2 allele alters responsiveness at lower levels of cholesterol intake remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 40 publications
4
36
2
1
Order By: Relevance
“…We did not find differences in baseline lipid levels between carriers of the APOA4-2 allele and carriers of APOA4-1/1, a finding also reported by McCombs et al 17 in normolipidemic subjects. On the other hand, baseline plasma apoB concentrations were significantly lower in our APOA4-2 subjects.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We did not find differences in baseline lipid levels between carriers of the APOA4-2 allele and carriers of APOA4-1/1, a finding also reported by McCombs et al 17 in normolipidemic subjects. On the other hand, baseline plasma apoB concentrations were significantly lower in our APOA4-2 subjects.…”
Section: Discussionsupporting
confidence: 74%
“…This hypolipidemic response was similar to what has been described for LDL-C when non-FH individuals consume a low-fat diet. 16,17 Surprisingly, these effects observed for apoB were not paralleled by those observed for LDL-C, for which no allelic differences in dietary response could be demonstrated. These data suggest that dietary intervention may induce remodeling of the LDL particles in Data are meanϮ SD.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, none of the previous studies controlled for known variations in cholesterol absorption associated with apo E or apo A-IV genotypes and all had less stringent dietary control than in this investigation. 16,44,45 Although a recent study showed no difference between different apo E alleles on cholesterol absorption and metabolism, 46 this observation awaits further confirmation because previous studies demonstrated apo E genotype-related differences in cholesterol absorption. 44,45,47,48 In summary, in a healthy population with apo A-IV 1/1 and apo E 3/3 genotypes, supplementation with CDCA or DCA enriched bile with the corresponding bile acid.…”
Section: Discussionmentioning
confidence: 68%